Effect of feeding Mentha piperita (Pudina) on nutrient balance and blood biochemical of small ruminants - Bhat, Asif Rasool; Ishfaq, Ahmad; Ganai, Abdul Majeed; Beigh, Yasir Afzal; Sheikh, Gowhar Gull (Indian Journal of Animal Nutrition, 2019)
The study was taken to evaluate the effects of Mentha piperita(Pudina),a herbal feed additive, on the nutrient balance and blood biochemical in sheep.Ten male adult Bakerwal sheep were divided in to control (T0) and treatment (T1) groups. The complete ration for T1was fortified with herbMentha piperita@3%, level per pre-determined by in vitrodigestibility experiment.DM intake, OM intake, average daily gainand digestibility coefficients of DM, OM, CP and EE showed significant (P